2021
DOI: 10.1177/08902070211040975
|View full text |Cite
|
Sign up to set email alerts
|

Character Growth Following Collective Life Events: A Study on Perceived and Measured Changes in Character Strengths During the First Wave of the COVID-19 Pandemic

Abstract: Did the COVID-19 pandemic promote character growth? Studies using sequential samples suggest that collective life events can result in character growth, but their conclusions have been questioned. This study used three approaches to examine character growth during the first wave of the pandemic: perceived changes in oneself and in a close other, and a longitudinal analysis of changes. In addition, we tested whether character strengths assessed before the pandemic predicted specific instances of growth, that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Such studies show remarkable stability pre-and post-event across a range of outcomes, including 10.3389/fpsyg.2022.1012120 empathy, life satisfaction, religiosity, and personality (Milojev et al, 2014;Chopik et al, 2021Chopik et al, , 2022Blackie and McLean, 2022;Dorfman et al, 2022;Fassbender et al, 2022;Forgeard et al, 2022;Jayawickreme et al, 2022;Reitz et al, 2022). Thus, stability or declines in functioning appear to be the more typical response to adversity, with growth or positive change being much less prevalent than suggested by prior cross-sectional research (Frazier et al, 2009;Davis et al, 2021;Rakhshani and Furr, 2021;Gander and Wagner, 2022;Infurna et al, 2022;Laceulle et al, 2022;Serrano et al, 2022). However, two primary shortcomings in current longitudinal research limit conclusions about growth or resilience.…”
Section: Introductionmentioning
confidence: 94%
“…Such studies show remarkable stability pre-and post-event across a range of outcomes, including 10.3389/fpsyg.2022.1012120 empathy, life satisfaction, religiosity, and personality (Milojev et al, 2014;Chopik et al, 2021Chopik et al, , 2022Blackie and McLean, 2022;Dorfman et al, 2022;Fassbender et al, 2022;Forgeard et al, 2022;Jayawickreme et al, 2022;Reitz et al, 2022). Thus, stability or declines in functioning appear to be the more typical response to adversity, with growth or positive change being much less prevalent than suggested by prior cross-sectional research (Frazier et al, 2009;Davis et al, 2021;Rakhshani and Furr, 2021;Gander and Wagner, 2022;Infurna et al, 2022;Laceulle et al, 2022;Serrano et al, 2022). However, two primary shortcomings in current longitudinal research limit conclusions about growth or resilience.…”
Section: Introductionmentioning
confidence: 94%
“…So far, there are very few studies investigating the detailed changes in the 24 character strengths related to the pandemic. Gander and Wagner [ 22 ] measured three kinds of character strengths changes (i.e., self-perceived changes, perceived changes in close others, and the actual differences before and after the first wave of the pandemic) in a German-speaking area by a longitudinal study ( n = 372) comparing the first and the second pandemic wave. Although most of the character strengths except zest, hope, humor, and self-regulation showed perceived increases in the self and close others, none of the character strengths carried significant changes in actual differences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As COVID-19 is concerned, empirical studies have also reported positive relations between character strengths and mental health, indicated by post-traumatic growth during and after the first pandemic wave [ 21 , 22 , 23 , 24 , 25 ]. Character strengths could moderate between COVID-19-related stress and well-being [ 23 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations